#TITLE_ALTERNATIVE# - PURNAMASARI (NIM : 10106040); Pembimbing : Prof. Dr. Roberd Saragih, WULAN
Portfolio optimization is a way / method used to obtain the optimal portfolio. Optimal portfolio is a portfolio that has the highest expected return with low risk of loss. Currently, many methods have been used to obtain the optimal portfolio, including using present value analysis, mean-variance analysis, a variety of optimal control and a lot of simulation. In this final project, we will discuss two methods to obtain the optimal portfolio. In the first method, the optimal portfolio will be determined without the use of control is by using the model random walk. While the second method, the optimal portfolio will be determined by applying a stochastic optimal control. The proportion that produced the optimal portfolio will be determined by two methods. Furthermore, the optimal portfolio obtained from the two models are simulated to show that the portfolio obtained from the model is the optimal portfolio.